Herman-Wallis correction in vibrational CARS of oxygen - Marrocco, Michele (Journal of Raman spectroscopy, 2011)
Light molecules are subject to vibration–rotation (VR) interaction, which implies corrections to the rigid rotor approximation and, in particular, corrections to spectral line intensities are related to the so‐called Herman–Wallis (HW) factor. This problem is outlined here for the spectral response of some medium‐weight diatomics in the gas phase and probed by means of vibrational coherent anti‐Stokes Raman scattering (CARS) used for diagnostic reasons in combustion science. However, different from other works on this subject, we specialized our analysis to oxygen and, since the peculiarity of its anti‐bonding molecular orbital, we find that the VR coupling is responsible for deviations that compete with the effect of Raman line widths typical of collisional environments of hot gases at room pressure. The HW correction is ultimately demonstrated to affect O2 CARS thermometry in such a manner that the accuracy for measurements at high temperatures can be improved. Copyright © 2011 John Wiley & Sons, Ltd. Vibration‐rotation interaction generates corrections to spectral line intensities. Such problem is here outlined for the spectral response of some medium‐weight diatomics in the gas phase and probed by means of vibrational coherent anti‐Stokes Raman scattering (CARS). Emphasis is on oxygen for the peculiarity of its anti‐bonding molecular orbital.